Efeitos do ensino do ecoico generalizado na emergência de prosódia para crianças com Autismo - Magalhães, Aline de Fátima Rosa (Universidade Federal de São Carlos, 2026)
The objective of the study was to experimentally evaluate the effects of teaching generalized echoic verbal operants on the emergence of prosody in children with ASD. To this end, a study was conducted using a non-concurrent multiple baseline design between participants. The dependent variables (DVs) in this study correspond to echoic responses, direct teaching of multiple echoic samples, and prosody, the acquisition of which will not be taught directly, but only measured to verify possible side effects or generativity processes resulting from the teaching of multiple echoic samples. The independent variable (IV) consisted of the direct teaching of multiple examples of verbal auditory stimuli, implemented systematically throughout the sessions, investigating their effects on both the emergence and acquisition of prosodic repertoires. Five children diagnosed with ASD, aged between four and seven years, participated in the study. The results indicated that teaching multiple instances of echolalia produced consistent increases in prosodic performance percentages throughout the sessions. The observed effects can be explained by the formation of auditory-auditory equality relations and the transfer of control of this relation across new stimuli. Point-to-point correspondence expanded from words to new and socially relevant acoustic properties, and such changes have direct implications for the social function of language, including reading, writing, and literacy.
Effects of generalized echoic teaching on the emergence of prosody in children with autism
Keywords: Educação Especial; Ecoico generalizado; Autismo; Prosódia; Relação de igualdade; Special Education; Generalized echoic; Autism; Prosody; Equality relations; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade